Synthesis and properties of thallium based superconducting wire and tape - Wivell, S; Fox, S; Moore, J; Grovenor, C (IEEE, 1995)
We are investigating the potential for wire fabrication in the one-layer thallium superconducting systems by comparing the properties of wires and tapes prepared with the Tl-Sr-Ca-Cu-O and Tl-Ba-Ca-Cu-O phases doped with a variety of elements; in particular the (Tl/Pb)-(Sr/Ba)-Ca-Cu-O and (Tl/Bi)-(Sr/Ba)-Ca-Cu-O phases. The purpose of this investigation is to identify the one layer thallium phase which is most appropriate for the fabrication of a demonstrator magnet operating at 77K. This paper will report on the combination of drawing and rolling operations which produces the best core uniformity, and the heat treatment processes that give the most reliable high Jc values. Short length Jc values as high as 9 kAcm-2 have been achieved, and some progress made in the fabrication and testing of longer lengths.